Putamen volume correlates with obsessive compulsive characteristics in healthy population. (30th March 2016) - Kubota, Yasutaka; Sato, Wataru; Kochiyama, Takanori; Uono, Shota; Yoshimura, Sayaka; Sawada, Reiko; Sakihama, Morimitsu; Toichi, Motomi
Abstract: Obsessions and compulsions (OCs) are frequent in healthy subjects; however neural backgrounds of the subclinical OCs were largely unknown. Results from recent studies suggested involvement of the putamen in the OC traits. To investigate this issue, 49 healthy subjects were assessed using structural magnetic resonance imaging (MRI) and the Maudsley Obsessive Compulsive Inventory (MOCI). Anatomical delineation on MRI yielded the global volume and local shape of the putamen. Other striatal structures (the caudate nucleus and globus pallidus) were also examined for exploratory purpose. The relationship between volume/shape of each structures and MOCI measure was analyzed, with sex, age, state anxiety, trait anxiety, and full-scale Intelligence Quotient regressed out. The volume analysis revealed a positive relationship between the MOCI total score and the bilateral putamen volumes. The shape analysis demonstrated associations between the higher MOCI total score and hypertrophy of the anterior putamen in both hemispheres. The present study firstly revealed that the volume changes of the putamen correlated with the manifestation of subclinical OC traits. The dysfunctional cortico-anterior striatum networks seemed to be one of the neuronal subsystems underlying the subclinical OC traits. Highlights: We demonstrated that the bilateral putamen enlargements correlate with the subclinical OC traits. The observed putamen enlargement may most prominently reflect the doubting subdimension of the OC traits. The putamen enlargements may reflect the dysfunctional cortico-anterior striatum networks underlying the subclinical OC traits. The shape abnormality of the putamen might reflect cognitive abnormality such as automatic/repetitive pattern of thinking underlying the OCD pathology.